A dictionary of religion and religions, including theological and ecclesiastical terms - Ince, Richard Basil (A. Barker London, 1935)
"A Dictionary of Religion and Religions, Including Theological and Ecclesiastical Terms" serves as a comprehensive reference tool, offering definitions and explanations of key concepts, terms, and practices across various religions and theological frameworks.